Comparison of Fork‐tip and Franseen needles for endoscopic ultrasound‐guided fine‐needle biopsy in pancreatic solid lesions: A propensity‐matched analysis. Issue 1 (28th June 2022) - Fujita, Akashi; Ryozawa, Shomei; Tanisaka, Yuki; Ogawa, Tomoya; Saito, Yoichi; Katsuda, Hiromune; Miyaguchi, Kazuya; Yasuda, Masanori; Araki, Ryuichiro; Mashimo, Yumi; Tashima, Tomoaki; Nakano, Yuya; et al.
Abstract: Objectives: There is no unanimity regarding the most appropriate needle to use for an endoscopic ultrasound‐guided fine‐needle biopsy (EUS‐FNB). To date, new types of FNB needles have been designed, including the Fork‐tip and Franseen needles. This study primarily aimed to compare the diagnostic accuracy and histological quality between the use of the Franseen and Fork‐tip needles in EUS‐FNB for solid pancreatic lesions. Materials and methods: We retrospectively analyzed 147 patients at our center for solid pancreatic lesions, 75 of whom underwent EUS‐FNB using a 22‐G Franseen needle, and 72 using a 22‐G Fork‐tip needle, from December 2019 to September 2021. The present study conducted a propensity‐matched analysis and confounder adjustment. Results: The diagnostic accuracy of the Fork‐tip group (93.3%, 42/45) was the same as that of the Franseen group. For the core tissue and blood scores, no significant difference was observed ( p = 0.58, 0.25) between the two groups. The rate of changes in the operator from that of a trainee to an expert was less in the Fork‐tip group (4.4%, 2/45) than in the Franseen group (15.6%, 7/45), but not significantly different ( p = 0.16). Conclusions: In both groups, the diagnostic accuracy and histological quality were not significantly different. Additionally, there were no significant differences in the rate of operator changes. As both needles are useful, the choice of using either of them is equally good.